A Review of Child Abuse in India: Exploring the prevalence and challenges of child abuse in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Child abuse by another person, whether adult or kid, harms or neglects a child from it. In all cultural, ethnic and socioeconomic groupings, child abuse occurs. Misuse of children may be physical, verbal, emotional, sexual or neglective. Abuse may cause a kid significant damage and even death. A issue that in India has barely begun to emerge The global challenges of gender violence include rape, sexual abuse and sexual harassment.